The Social Bifurcation of Reality: Symmetrical Construction of Knowledge in Science-Trusting and Science-Distrusting Discourses - Rughiniş, Cosima; Flaherty, Michael G. (Frontiers in Sociology, 2022)
This article proposes a conceptual framework to study the social bifurcation of reality in polarized science-trusting and science-distrusting lay worldviews, by analyzing and integrating five concepts: science work, number work, emotion work, time work, and boundary work. Despite the epistemological asymmetry between accounts relying on mainstream science and science-distrusting or denialist ones, there are symmetrical social processes contributing to the construction of lay discourses. Through conceptual analysis, we synthesize an alternative to the deficit model of contrarian discourses, replacing the model of social actors as “defective scientists” with a focus on their culturally competent agency. The proposed framework is useful for observing the parallel construction of polarized realities in interaction and their ongoing articulation through hinge objects, such as vaccines, seatbelts, guns, or sanitary masks in the Covid-19 context. We illustrate the framework through a comparative approach, presenting arguments and memes from contemporary online media in two controversies: namely, vaccine-trusting versus vaccine-distrusting views and Covid-convinced versus Covid-suspicious discourses.